An investigation into the financial sustainability of Islamic Saving, Credit Cooperative Society (SACCOS) in Tanzania - Said, Mariam Swalehe; Annuar, Hairul Azlan; Hamdan, Hamdino (Emerald Group Publishing Limited, 2019)
The purpose of this paper is to assess the financial sustainability of Islamic Saving Credit Corporative Society (SACCOS) and the factor(s) affecting their financial sustainability in the Tanzanian context.The data set used in this study comes from four SACCOS audited financial reports from the year 2010 to 2014 and from interviews with SACCOS’s management.The study found that the IMFIs in Tanzania are not financially sustainable. Additionally, having responsible staff members, regular review of financial guidelines, education to members, cooperation between employees and management and staff training are found to be highly contributing factors towards SACCOS’s financial sustainability. Moreover, the findings reveal that depending on the single source of income, i.e., charges on members contributed much in these SACCOS’s not being financially sustainable.Only two available registered Islamic SACCOS was used. Additionally, conventional SACCOS have been in service provision for a long time as compared to Islamic ones; hence, caution must be taken for comparison purposes. Based on these findings, the Islamic SACCOS needs to initiate productive projects that can enable them to have other income sources apart from charges on members. This study traces the financial trend of Islamic SACCOS in Tanzania since its establishment in 2010. Such trace enables Islamic SACCOS and other stakeholders to be aware on the financial progress of Islamic SACCOS and act accordingly to ensure sustainability.